Answers to the Comments on the article “Monitoring COVID-19 is like instrument flying” submitted by David D. Pokrajac - Kočović, Petar (Vojnotehnički glasnik / Military Technical Courier, 2021)
Answers to the Comments on the article “Monitoring COVID-19 is like instrument flying” submitted by David D. Pokrajac.